From victim to survivor: the girls of water and rice. Issue 3 (November 2015) - Reed, Charlotte V.
Abstract : This personal reflection is based on key lessons that have emerged as a result of a year of fieldwork with female (former) child soldiers in reintegration programmes in Colombia. In working with, and observing, a local non-profit organisation in Bogotá, Colombia, it became evident that assisting the girls in transitioning from a victim mentality to that of a survivor was critical to successful reintegration. This reflection seeks to demonstrate the important work being undertaken in Colombia, and highlights the importance of this transition, which ideally can influence reintegration programmes on a global scale.